2016
DOI: 10.1002/chem.201603557
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional RuII‐Complex‐Catalysed Tandem C−C Bond Formation: Efficient and Atom Economical Strategy for the Utilisation of Alcohols as Alkylating Agents

Abstract: Catalytic activities of a series of functional bipyridine-based Ru complexes in β-alkylation of secondary alcohols using primary alcohols were investigated. Bifunctional Ru complex (3 a) bearing 6,6'-dihydroxy-2,2'-bipyridine (6DHBP) ligand exhibited the highest catalytic activity for this reaction. Using significantly lower catalyst loading (0.1 mol %) dehydrogenative carbon-carbon bond formation between numerous aromatic, aliphatic and heteroatom substituted alcohols were achieved with high selectivity. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…When tris‐NHC‐Ir III 3 a‐2H was heated in a mixture of CH 3 OH/CD 3 OD (1:1) with an excess amount of KOH at 60 °C for 1 hour (conditions similar to the cross‐coupling reaction), two hydride signals appeared at −8.53 and −11.70 ppm, (Figure b). The correlation of the two hydrides in two‐dimensional correlation spectroscopy (2D‐COSY) revealed that the hydrides adopt a cis configuration (Figure S30), similar to that previously reported for pincer complexes . Almost identical hydride signals were detected in the 1 H NMR spectrum of tris‐NHC‐Ir I 3 b with KOH in a hot mixture of CH 3 OH/CD 3 OD (Figure b), implying that tris‐NHC‐Ir I 3 b could be converted into cis ‐dihydride species tris‐NHC‐Ir III 3 b‐2H , the formation of which was further supported by a 2D‐COSY study (Figure S31).…”
Section: Figuresupporting
confidence: 79%
“…When tris‐NHC‐Ir III 3 a‐2H was heated in a mixture of CH 3 OH/CD 3 OD (1:1) with an excess amount of KOH at 60 °C for 1 hour (conditions similar to the cross‐coupling reaction), two hydride signals appeared at −8.53 and −11.70 ppm, (Figure b). The correlation of the two hydrides in two‐dimensional correlation spectroscopy (2D‐COSY) revealed that the hydrides adopt a cis configuration (Figure S30), similar to that previously reported for pincer complexes . Almost identical hydride signals were detected in the 1 H NMR spectrum of tris‐NHC‐Ir I 3 b with KOH in a hot mixture of CH 3 OH/CD 3 OD (Figure b), implying that tris‐NHC‐Ir I 3 b could be converted into cis ‐dihydride species tris‐NHC‐Ir III 3 b‐2H , the formation of which was further supported by a 2D‐COSY study (Figure S31).…”
Section: Figuresupporting
confidence: 79%
“…Furthermore, several viable Ir and Ru catalysts ( 4 – 10 ) that exhibited a good catalytic activity in several dehydrogenative and cross‐coupling reactions were also investigated (Figure ). Among them, the pincer‐type Ru‐PNP complexes ( 9 and 10 ) displayed good TOFs (around 900 h −1 ), further attesting the superior catalytic activity of 3 b (TOF around 2000 h −1 ). When the catalyst loading of 3 b was reduced to 250 ppm, a TOF value as high as 3540 h −1 was obtained (Figure ), and a slightly higher TOF of 3660 h −1 was observed with the solid 3 b‐2 H .…”
Section: Figurementioning
confidence: 99%
“…In 2016, Kundu and co-workers synthesized 6,6'-dihydroxy-2,2'-bipyridine (6DOHBP) based few ruthenium complexes and examined their catalytic activity towards the β-alkylation of secondary alcohols with primary alcohols. [37] Among a variety of functionalized 2,2'-bipyridine based Ru-complexes, complex 10 a displayed the superior activity. 6DOMeBP ligand containing similar metal complex (10 b) showed lower reactivity in this reaction.…”
Section: D-metal Based Complexesmentioning
confidence: 99%